PINPOINT® can be used for photodynamic diagnosis based on 5-aminolevulinic acid-induced protoporphyrinIX in gastric cancer surgery: Report of a case. (2020) - Kamada, Teppei; Yoshida, Masashi; Ohdaira, Hironori; Hoshimoto, Sojun; Narihiro, Satoshi; Suzuki, Norihiko; Marukuchi, Rui; Takeuchi, Hideyuki; Suzuki, Yutaka
Highlights: We have reported the case that underwent laparoscopic total gastrectomy with photodynamic diagnosis based on 5-aminolevulinic acid induced protoporphyrinIX by using PINPOINT®. PINPOINT®, a brightfield color fluorescence camera, could be used for 5-ALA-PDD. Administration of 5-ALA through PTEG for a patient with pyloric stenosis was successfully performed. Abstract: Introduction: Photodynamic diagnosis (PDD) using 5-aminolevulinic acid (5-ALA) has been used as a diagnostic procedure for malignant diseases. Dedicated laparoscopes (e.g., an IMAGE1 Camera System®) are used for this procedure. We report a case treated with laparoscopic total gastrectomy with 5-ALA-PDD using the PINPOINT® system. Presentation of case: A patient in his 80 s with diffuse-type gastric cancer with pyloric stenosis and ascites was admitted to our hospital. Double percutaneous transesophageal gastrotubing (dPTEG) for both gastric decompression and enteral nutrition and two cycles of preoperative chemotherapy with S-1 plus oxaliplatin were performed preoperatively. Additionally, we preoperatively performed an ex vivo experiment that confirmed that the PINPOINT® system can be used to observed protoporphyrin IX (PpIX) fluorescence. Three hours before surgery, 5-ALA hydrochloride was administered through dPTEG. Observation was performed by PINPOINT®, and Aladuck® was used as an excitation light source. Peritoneal nodules and sampled lymph nodes with red fluorescence were observed by 5-ALA-PDD. Accordingly, we gave up a radical operation and laparoscopic total gastrectomy without systematic lymphadenectomy to improve anemia and release pyloric stenosis was performed. The patient's postoperative course was uneventful. Discussion: It is possible that the connection with each of the scopes and an exclusive light source (Aladuck®) enable the easy use of 5-ALA-PDD without dedicated laparoscopy. It is expected that 5-ALA-PDD would show the further spread of gastrointestinal cancer if it could be performed with many types of laparoscopes. Conclusion: We found that 5-ALA-PDD-guided surgery can be easily performed in a short time using the PINPOINT® system.